Challenges in patient selection for the parachute device implantation. Issue 5 (8th August 2013) - Bozdag‐Turan, Ilkay; Bermaoui, Benjamin; Paranskaya, Liliya; GökmenTuran, R.; D'Ancona, Giuseppe; Kische, Stephan; Birkemeyer, Ralph; Jovanovic, Bojan; Schuetz, Jan; Akin, Ibrahim; Turan, Cem Hakan; Ortak, Jasmin; et al.
<x xml:space="preserve">Abstract</x> Background A novel percutaneous ventricular restoration therapy (PVRT) has been recently proposed to treat patients with ischemic heart failure (IHF) and antero‐apical regional wall motion abnormalities after myocardial infarction (MI). In this prospective, single center, non‐randomized study, we herein propose safety and feasibility evaluation of the device, in which a different patient selection strategy was used. Material and Methods A three‐stage evaluation was adopted in a series of patients referred for a Parachute Ventricular Partitioning Device (ParachuteTM). After an initial clinical evaluation, a secondary screening step was performed according to echocardiographic functional (LVEF<40%, apical/anterior akinesia/dyskinesia) and anatomical criteria [diameter of LV‐apex (LVAD) = 4.0 × 5.0 cm, left ventricular end diastolic diameter (LVEDD)>56 mm, left ventricular end systolic diameter (LVESD)>38 mm]. Patients encountering the echocardiographic criteria were selected for 3D cardiac CT (architecture, geometry, and trabeculation of the left ventricle) and eventually treated with the ParachuteTM. Results Fifty patients were screened according to the echocardiographic criteria. Twenty‐seven of those that met the echo inclusion criteria underwent further cardiac CT imaging. After CT imaging, eight patients were scheduled for ParachuteTM implantation. The device was successfully implanted in all eight patients with no in‐hospital mortality. A 3‐month follow‐up echocardiography showed LV‐volume reduction [95% CI; LVEDV: −76.5 (−116; −36.8), P = 0.002 and LVESV: −47.4 (−63.8; −30.9), P = 0.003] and improvement of global EF [95% CI; global EF: 6.87 (5.36; 8.39), P = 0.008]. Conclusion Selection criteria for ParachuteTM placement should include left ventricular functional and anatomical parameters. When preprocedural echocardiography and cardiac CT are adequately implemented, satisfactory periprocedural and short term follow‐up results may be achieved after ParachuteTM implantation. © 2013 Wiley Periodicals, Inc.